Invasive pulmonary aspergillosis in COVID-19 patients - V. G. Gusarov; M. N. Zamyatin; D. A. Kamyshova; V. S. Fomina; Yu. A. Abovich; N. V. Lovtsevich; O. Yu. Bronov; L. V. Petrova; T. S. Sysoeva; V. I. Vasilashko; O. V. Shadrivova; N. N. Klimko (Журнал инфектологии)
A retrospective analysis of the medical data of 12 patients with COVID-19 was performed. For the diagnosis of invasive aspergillosis the international criteria ECMM/ISHAM 2020 were used. We analyzed the scientific literature data on the diagnosis and treatment of invasive aspergillosis in patients with COVID-19.Results. Among the 12 examined patients with a severe course of COVID-19, invasive aspergillosis was diagnosed in 5 patients. Four patients (80%) were treated in the ICU. Steroids or interleukin-6 inhibitors were used in 80% patients. Severe lymphocytopenia was in 80% patients, neutropenia 20%. A fever refractory to antibiotic therapy was noted in 80% patients, an increase in respiratory failure – 60%, acute respiratory distress syndrome – 60%. All patients showed negative dynamics of changes in the chest CT scan. Invasive aspergillosis was confirmed with a positive test for galactomannan in bronchoalveolar lavage and / or serum in 100% of cases. All patients received antifungal therapy with voriconazole and/or caspofungin. The overall 12-week survival rate was 80%.Conclusion. In ICU patients with severe COVID-19 and progressive pulmonary symptoms invasive aspergillosis should be excluded. Examination of substrates from the lower respiratory tract (BAL, tracheal aspirate, or nonbronchoscopic lavage) is necessary. Laboratory examination should include microscopy, culture and test for galactomannan. Voriconazole and isavuconazole are drugs of choice for the treatment of invasive aspergillosis in patients with COVID-19.